Clinical, Etiological and Neuroimaging Profile in Children with Microcephaly Under Five Years of Age - Shazia Kulsoom, Shazia Soomro, Misbah Anjum, Erum Majid, Bader Faiyaz Zuberi, Rimsha Shahid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To describe the clinical, etiological and neuroimaging profile of children with microcephaly at a tertiary care children hospital of Karachi Study Design: Cross sectional study Place and Duration of Study: The study was conducted at neurology outpatient department of National institute of child health (NICH) Karachi from 1st December 2020 to 30th November 2021. Methodology: Patients with microcephaly who presented to outpatient department of National Institute of Child Health (NICH) Karachi were included. Clinical history and physical examination findings were recorded in proforma and neuroimaging was done in all patients including computed tomography or magnetic resonance imaging of brain. Data entry and analysis was done in SPSS 25.0. Results: Total 130 children were enrolled with mean age was 7.17 ±7.1 (range 1-41) months of which male were 57(43.5%) and females were 74(56.5%). Mean weight was 7.74 ±2.9 kg. Mean FOC was 40.6 ±3.3 (range 33-49) cm. common clinical symptoms for presentation were seizures 95 (73%) and developmental delay 95 (73%). Most frequent etiology was birth asphyxia 60 (46%), and neuroimaging shows brain atrophy in 32 (24%). Conclusion: In our study common cause of microcephaly was cerebral palsy and was commonly associated with of epilepsy, developmental delay, hearing and vision problems. Further plans are needed for prevention of perinatal asphyxia by regular antenatal checkups and delivery by trained person with co-ordination between pediatrician and obstetrics along with early identification of danger signs, which may improve outcome and prevent lifelong disabilities Keywords: Microcephaly; developmental delay; seizures.